EGFR-targeted poly(ethylene glycol)-distearoylphosphatidylethanolamine micelle loaded with paclitaxel for laryngeal cancer: preparation, characterization and in vitro evaluation. (18th August 2015) - Ren, Henglei; Gao, Chunli; Zhou, Liang; Liu, Min; Xie, Cao; Lu, Weiyue
Abstract: The objective of this study was to evaluate the potential of using polymeric micelles modified with a peptide (termed GE11) ligand of epidermal growth factor receptor as the targeted carriers to achieve increased accumulation in laryngeal cancer and enhanced intracellular delivery for the encapsulated anticancer drugs. Poly (ethylene glycol)-distearoylphosphatidylethanolamine (PEG-DSPE) micelles containing paclitaxel were prepared via film-hydration method followed by investigation of in vitro release of paclitaxel in phosphate-buffered saline. The average size of GE11-PEG-DSPE/paclitaxel micelle and mPEG-DSPE/paclitaxel were 35 ± 2.8 nm [the polydispersity index (PDI) = 0.207] and 28 ± 2.1 nm (PDI = 0.154), respectively. Micelles with or without GE11-modified had similar physicochemical properties. Transmission electron microscopy showed that the micelles were homogeneous and spherical in shape. Encapsulation efficiency and drug loading of the micelle were 74.11 ± 3.89% and 3.58 ± 2.82%, respectively. The in vitro targeting characteristic of GE11-modified micelles was investigated by observing the level of cellular uptake of fluorescent coumarin-6-loaded micelles on EGFR over-expressed human laryngeal cancer cell line Hep-2 and EGFR low-expressed human leukemic cell line U-937. Hep-2 cell proliferation was significantly inhibited by GE11-PEG-DSPE/paclitaxel micelle compared to mPEG-DSPE/paclitaxel micelle and Taxol in vitro . Our results suggested that GE11-PEG-DSPE micelle could be a promising strategy for enhancing paclitaxel's chemotherapeutic effects on EGFR over-expressed cancer cells.